Spin reversal and magnetization jumps in ErMexMn1-xO3 perovskites (Me = Ni, Co) - Pena, O.; Antunes, A. B.; Baibich, M. N.; Lisboa Filho, Paulo Noronha [UNESP]; Gil, V.; Moure, C. (Elsevier B.V., 2007)
The erbium-based manganite ErMnO3 has been partially substituted at the manganese site by the transition-metal elements Ni and Co. The perovskite orthorhombic structure is found from x(Ni) = 0.2-0.5 in the nickel-based solid solution ErNixMn1-xO3, while it can be extended up to x(Co) = 0.7 in the case of cobalt, provided that the synthesis is performed under oxygenation conditions to favor the presence of Co3+. Presence of different magnetic entities (i.e., Er3+, Ni2+, Co2+, Co3+, Mn3+, and Mn4+) leads to quite unusual magnetic properties, characterized by the coexistence of antiferromagnetic and ferromagnetic interactions. In ErNixMn1-xO3, a critical concentration x(crit)(Ni) = 1/3 separates two regimes: spin-canted AF interactions predominate at x < x(crit), while the ferromagnetic behavior is enhanced for x > x(crit). Spin reversal phenomena are present both in the nickel- and cobalt-based compounds. A phenomenological model based on two interacting sublattices, coupled by an antiferromagnetic exchange interaction, explains the inversion of the overall magnetic moment at low temperatures. In this model, the ferromagnetic transition-metal lattice, which orders at T-c, creates a strong local field at the erbium site, polarizing the Er moments in a direction opposite to the applied field. At low temperatures, when the contribution of the paramagnetic erbium sublattice, which varies as T-1, gets larger than the ferromagnetic contribution, the total magnetic moment changes its sign, leading to an overall ferrimagnetic state. The half-substituted compound ErCo0.50Mn0.50O3 was studied in detail, since the magnetization loops present two well-identified anomalies: an intersection of the magnetization branches at low fields, and magnetization jumps at high fields. The influence of the oxidizing conditions was studied in other compositions close to the 50/50 = Mn/Co substitution rate. These anomalies are clearly connected to the spin inversion phenomena and to the simultaneous presence of Co2+ and Co3+ magnetic moments. Dynamical aspects should be considered to well identify the high-field anomaly, since it depends on the magnetic field sweep rate. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: spin reversal; magnetic oxide; magnetization jump; magnetic exchange